RANCANG BANGUN E-COMMERCE UMKM BUDIDAYA TANAMAN BERBASIS WEBSITE DI KELURAHAN LUBUK MINTURUN - Izzati, Asri Rahmi; Huda, Yasdinul (Universitas Negeri Padang, 2021)
Design and Build E-Commerce UMKM Plant Cultivation Website Based in Lubuk Minturun Village, designed to provide convenience in buying plants without directly coming to the store which has been done manually, so an e-commerce system is designed that aims to make it easier for buyers or customers to carry out the search process products, plant orders, and online transactions. In this e-commerce system, the design uses the Waterfall method and applies the MVC (Model, View, Controller) technique which was developed with the PHP programming language, the Codeigniter framework, and the MySQL Database Management System used. This design will create a Website-based UMKM Plant Cultivation E-Commerce system and information related to the names, types, and prices of plants sold in each UMKM Cultivation of ornamental plants, an E-Commerce system that can be done online transactions with payment methods made through account transfer and COD system.